PENGARUH METODE HAFALAN AL-QUR’AN TERHADAP TINGKAT KECERDASAN SPIRITUAL SANTRI DI PONDOK PESANTREN DAARUL-ANBA - Hidayati, Yuni (Prodi PAI IAILM Suryalaya, 2019)
This study aims to determine how the influence of the Al-Qur'an memorization method on the level of spiritual intelligence of students in Daarul Anba Islamic boarding school, the approach used in this study is a quantitative approach, while the descriptive correlational research method. The results of this study are: 1) Description of the Al-Qur'an Memorization Method is very good. 2) Santri Spiritual Intelligence Level in Daarul-Anba Islamic Boarding School is in the Very Good category. 3) Based on the results of calculations that the significant correlation coefficient is indicated by the tcount = 1.797 greater than ttable = 0.3008 so that Ho is rejected and Ha is accepted, ie there is a significant correlation or relationship between the Al-Qur'an Memorization Method on the Level of Spiritual Intelligence Santri in Daarul-Anba Islamic Boarding School. The results also showed that the determination value of 7.29% was determined by the Qur'an recitation method which was quite good. And the remaining 92.71% is influenced by other factors not examined by researchers.